Impact of alcohol withdrawal training program on knowledge, attitude, and perception among healthcare providers in a hospital setting. (2nd January 2022) - Kumar, Padma Rani; Yee, Anne; Francis, Benedict
ABSTRACT: Background: Delirium tremens is a life-threatening complication of alcohol withdrawal, which is preventable by prompt recognition and management. This study aimed to evaluate the impact of an alcohol withdrawal training program on knowledge, attitude, and perception among healthcare providers in a hospital setting. Methods: This was a quasi-experimental study with a pre and post-test design conducted at the Department of Psychological Medicine, University Malaya Medical Center, Malaysia. A total of 36 participants consisted of postgraduate psychiatry trainees who underwent a 60-min online training program whereby pre- and post-training evaluation was done using a locally validated 21-item knowledge, attitude, perception questionnaire on alcohol withdrawal and the Clinical Institute Withdrawal Assessment for Alcohol–Revised (CIWA-Ar) scales. Results: There was a significant difference between pre- and post-training scores in knowledge, attitude, and perception domains ( p < .05). Furthermore, significant difference in pre- and post-training CIWA-Ar scores ( p < .05) were detected. Post-training CIWA-Ar score approached the true value and with minimal variation of scores among the participants. Conclusion: The alcohol withdrawal training program was clinically significant with an effect size of 0.75. It can be utilized to train healthcare providers from various departments treating alcohol withdrawal patients to ensure better standardization of care.